Perception toward the Use of TikTok Video in Learning Writing: A Survey Study at a Senior High School in Rambah Hilir - Syahla Putri Salsabil; Dedy Wahyudi (Lembaga penelitian dan pengabdian kepada masyrakat, 2023)
This study investigated students’ perception toward the use of TikTok video in learning to write procedure text. It employed a survey approach. There were 51 students as samples selected by using simple random sampling technique. This study utilized a questionnaire in collecting the data, which consist of 38 items of statement in three indicators (cognitive, affective, and conative). With reference to analysis, results indicate that the students’ perception toward the use of TikTok video in learning to write procedure text at Senior High School 2 Rambah Hilir are in the strongly positive category (52.94%) and the positive category (47.06%). To conclude, the students have strongly positive perceptions toward the use of TikTok video in learning to write procedure text in terms of cognitive, affective, and conative domains.